2016
DOI: 10.1038/nrneurol.2016.119
|View full text |Cite
|
Sign up to set email alerts
|

Social networks and neurological illness

Abstract: Every patient is embedded in a social network of interpersonal connections that influence health outcomes. Neurologists routinely need to engage with a patient’s family and friends due to the nature of the illness and its social sequelae. Social isolation is a potent determinant of poor health and neurobiological changes, and its effects can be comparable to those of traditional risk factors. It would seem reasonable, therefore, to map and follow the personal networks of neurology patients. This approach revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
68
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 65 publications
(70 citation statements)
references
References 54 publications
2
68
0
Order By: Relevance
“…This study has shown that, in a cohort of individuals with MSA and PSP and their carers, connection was a prevailing concern, with subthemes of affected social life, communication impairment, perception of stigma, and impact on relationships. In neurological disorders, it has been shown that individuals who have wider social networks and better support tend to have better outcomes [30]. Social isolation has been found to be a predictor for further ischaemic events after stroke [31].…”
Section: Discussionmentioning
confidence: 99%
“…This study has shown that, in a cohort of individuals with MSA and PSP and their carers, connection was a prevailing concern, with subthemes of affected social life, communication impairment, perception of stigma, and impact on relationships. In neurological disorders, it has been shown that individuals who have wider social networks and better support tend to have better outcomes [30]. Social isolation has been found to be a predictor for further ischaemic events after stroke [31].…”
Section: Discussionmentioning
confidence: 99%
“…Social networks and interpersonal interaction are critically involved in neurobiological processes (Dhand et al, 2016). This has been suggested in the literature both from animal models, showing that social isolation affects neuroplasticity in the mature brain, and from observational studies, showing that loneliness is associated with an increased risk of late-onset dementia and correlates with worse outcomes after stroke (Cacioppo, Fowler, & Christakis, 2009;Ieraci, Mallei, & Popoli, 2016;Wilson et al, 2007).…”
Section: So Cial C Apital and Neurolog Ic Al Conditionsmentioning
confidence: 92%
“…Dhand and colleagues have recently proposed a comprehensive framework for advancing social network science in neurology, which involves the characterization of social networks in patients with common neurological disorders, the identification of the mechanisms regulating the interplay between the social networks and neurological outcomes, and finally the evaluation of potential network interventions (Dhand et al, 2016). Dhand and colleagues have recently proposed a comprehensive framework for advancing social network science in neurology, which involves the characterization of social networks in patients with common neurological disorders, the identification of the mechanisms regulating the interplay between the social networks and neurological outcomes, and finally the evaluation of potential network interventions (Dhand et al, 2016).…”
Section: So Cial C Apital and Neurolog Ic Al Conditionsmentioning
confidence: 99%
“…The social impact of cardiovascular diseases is substantial and understudied 1. Contraction of patients’ social network occurs after stroke 2.…”
mentioning
confidence: 99%